2007
DOI: 10.4319/lom.2007.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of sediment phosphorus revisited. I: Fractionation steps and their biogeochemical basis

Abstract: Internal phosphorus (P) loading leading to accelerated eutrophication of marine systems has made acute the research on P chemistry in sediments. Studies on the P chemistry in lake and marine sediments are commonly based on fractionation, where P compounds are divided into several pools according to their solubility in or reactivity with various chemical solutions. Procedures typically begin with dilute extractants, which remove the most loosely bound P forms, and they proceed stepwise toward stronger extractan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 51 publications
(55 reference statements)
1
78
0
3
Order By: Relevance
“…La concentration de PT a été déterminée à l'aide de la méthode standard SW 846-6010B de la United States Environmental Protection Agency. Les concentrations de s-P et de Fe-P ont été mesurées par extraction séquentielle selon une méthode décrite dans LUKKARI et al (2007a). Tous les résultats ont été reportés en poids sec (mg•g -1 ).…”
Section: éChantillonnage Et Analyse Des Sédimentsunclassified
“…La concentration de PT a été déterminée à l'aide de la méthode standard SW 846-6010B de la United States Environmental Protection Agency. Les concentrations de s-P et de Fe-P ont été mesurées par extraction séquentielle selon une méthode décrite dans LUKKARI et al (2007a). Tous les résultats ont été reportés en poids sec (mg•g -1 ).…”
Section: éChantillonnage Et Analyse Des Sédimentsunclassified
“…In our procedure, NH 4 Cl was replaced with NaCl in the first step of the extraction to minimize the dissolution of Ca-bound P (Lukkari et al 2007). For each sediment, a 0.5 g (dry weight) sample was sequentially extracted with (1) 0.46 M NaCl under an N 2 environment for 1 h to obtain loosely bound and pore water P; (2) 0.11 M sodium dithionite (Na 2 S 2 O 4 ) in 0.11 M sodium bicarbonate (NaHCO 3 ) buffer (pH 7) under an N 2 environment for 1 h to obtain P bound primarily to redox-sensitive Fe-oxides (NaBD-P i ) and organic P that is easily mineralized (NaBD-P o ); (3) 0.1 M NaOH for 18 h to obtain inorganic P (NaOH-P i ) associated with amorphous and some crystalline Al oxides but that may contain Fe-associated P not extracted in the previous step, as well as organic P (NaOH-P o ) associated with humic compounds and polyphosphates; (4) 0.5 M HCl for 1 h to extract Ca-associated P found predominantly in apatite minerals (HCl-P i ); and (5) 1 M NaOH at 85°C for 1 h to extract residual and recalcitrant forms of occluded P (85°NaOH-P).…”
Section: Sediment P Sequential Fractionationmentioning
confidence: 99%
“…Organic P (P o ) was estimated as the difference between P t and P i . NaBD extracts were sparged with He to remove dithionite prior to determining P colorimetrically, as it interferes with the development of the phosphomolybdate complex (Lukkari et al 2007). …”
Section: Sediment P Sequential Fractionationmentioning
confidence: 99%
“…Plausibility tests determining simultaneously mobilized metals (Jensen and Thamdrup 1993, Ulrich 1997, Kopaček et al 2005, Lukkari et al 2007, the use of model substances such as activated sludge (Uhlmann et al 1990), or combining sequential P extraction with other structural analyses such as X-rays (Hupfer et al 1995) and 31 P NMR spectroscopy (Hupfer et al 2004, Ahlgren et al 2005 have shown that individual P species can be assigned accurately to a specific chemical fraction. Dissolution and subsequent rebinding of P within one step, however, negatively affects accurate P assignment (Barbanti et al 1994).…”
Section: Introductionmentioning
confidence: 99%